Novel Citric Acid Dendritic Hydrogels for the Delivery of Econazole Nitrate and its Antifungal Activity - B. Narasimha Rao, S. Rahath Fathima, V. Viswanath, K Gnana Prakash, D. Sai Padmini, P. Salomi Reddy (Journal of Applied Pharmaceutical Science, 2016)
Econazole is an imidazole derivative antifungal drug with distinguished antifungal properties. But the bioavailability of conventional econazole preparations is poor because of poor solubility and lipophilicity or lipophilic nature. Thus frequent application of the preparation is required to maintain therapeutic levels at the site of action. Such repeated doses may produce toxic affects thereby limiting the clinical use of the drug. Citric acid dendrimers give an opportunity to overcome the above limitations by improving its solubilization and drug permeation properties. Thus, the aim of current study is to design citric acid dendrimer hydrogels and study its influence on the drug release and anti-fungal activity of loaded drug. Dendritic architecture and size strongly influences the invitro release and antifungal activity of drug. Antifungal activity of designed Econazole hydrogel was measured by Agar plate diffusion method. Zone of inhibition values showed that citric acid dendrimers considerably enhanced the antifungal activity of Econazole to a greater extent and the effect was more with lower generation hydrogels. The operative mechanism is probably the smaller size (G2) that penetrates the fungal cell membrane more efficiently than higher generation (G3 and G4) hydrogels.
Keywords: Citric acid dendrimer,Econazole,Hydrogels,Antifungal activity,lipophilicity.